1995
DOI: 10.1002/em.2850250105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of X‐irradiation on mouse testicular cells and sperm chromatin structure

Abstract: The testicular regions of male mice were exposed to x-ray doses ranging from 0 to 400 rads. Forty days after exposure the mice were killed and the testes and cauda epididymal sperm removed surgically. Flow cytometric measurements of acridine orange stained testicular samples indicated a repopulation of testicular cell types following x-ray killing of stem cells. Cauda epididymal sperm were analyzed by the sperm chromatin structure assay (SCSA), a flow cytometric measurement of the susceptibility of the sperm n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
0
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 42 publications
8
91
0
4
Order By: Relevance
“…The changes in color were a reflection of reduction in sperm concentration and mass activity during insulation and post-insulation untreated phases and this is similar to findings by Matthew et al (1975). All the changes in color and reduction in semen characteristics have been attributed to a reduction in spermatids and spermatozoa number by a failure of spermatocyte cell stage to complete their maturation cycle (Sailer et al, 1997). The spermatocytes are the most susceptible cell type to heat; they are usually destroyed during scrotal insulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in color were a reflection of reduction in sperm concentration and mass activity during insulation and post-insulation untreated phases and this is similar to findings by Matthew et al (1975). All the changes in color and reduction in semen characteristics have been attributed to a reduction in spermatids and spermatozoa number by a failure of spermatocyte cell stage to complete their maturation cycle (Sailer et al, 1997). The spermatocytes are the most susceptible cell type to heat; they are usually destroyed during scrotal insulation.…”
Section: Discussionmentioning
confidence: 99%
“…Semen samples were collected from all animals using the electro-ejaculation method (Sailer et al, 1997) as control to the experiment on weekly basis for 3 weeks prior to insulation (preinsulation phases). This was to obtain the normal baseline values of the semen characteristics of the 12 bucks.…”
Section: Semen Collectionmentioning
confidence: 99%
“…This phenomenon has also been observed in male germ cells [de Boer et al, 2010]. Spermatogonial irradiation causes delayed genomic instability in descendant sperm [Sailer et al, 1995;Haines et al, 2001Haines et al, , 2002Cordelli et al, 2003] as well as in the progeny of irradiated male parents in rodents [Baulch and Raabe, 2005;Barber and Dubrova, 2006;Barber et al, 2009] and humans [Aghajanyan et al, 2011]. Remodeling of chromatin domains and nuclear matrix during spermiogenesis and in the zygote has been suggested to play a role in these phenomena [de Boer et al, 2010], but how and when they operate is still unclear.…”
Section: Introductionmentioning
confidence: 94%
“…Mechanistic understanding of non-targeted effects on the germ line is necessary to determine whether it is relevant for genetic risk assessment of radiation exposure. Mouse spermatozoa derived from irradiated premeiotic germ cells carry DNA strand breaks [Sailer et al, 1995;Haines et al, 2001Haines et al, , 2002Cordelli et al, 2003]. The persistence of these strand breaks is incompatible with the multiple mitotic cycles and checkpoints, meiosis and postmeiotic differentiation processes that take place in cells from the time of exposure to the generation of spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…genetic or developmental abnormalities) or due to secondary or extrinsic factors causing testicular or posttesticular injury (e.g. gonadotoxins, hyperthermia, oxidants, endocrine abnormalities) [2][3][4][5][6][7][8][9][10]. Investigators have suggested that protamine deficiency (with aberrant chromatin remodeling), reactive oxygen species (ROS) and abortive apoptosis may cause sperm DNA damage [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%